PENGEMBANGAN MEDIA PEMBELAJARAN SEJARAH MELALUI PEMANFAATAN WEBSITE PADA KELAS XII TKJ 2 SMK NEGERI 1 BANAWA KABUPATEN DONGGALA - Risma, Risma (Katalogis, 2016)
This research aims at producing media based-learning history through website use to the twelfth Grade Students at TKJ 2 SMK Negeri 1 Banawa Donggala Regency. The media developed was consisteds of two component,such as: material and learning media. The development was carried out through berg model and Gall model. The media developed was validated by material expert and media expert. The result of validation revealed that the media is in category of very good. Therefore, it can beconcluded that the development of media-based learning history through website use is proper to improve concept understanding in learning process.